2020
DOI: 10.1002/slct.201904348
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Application of Cyclodextrin‐Containing UV‐Curable Waterborne Polyurethane Based on Guest Regulation

Abstract: A novel UV‐curable supramolecular waterborne polyurethane (PU) was prepared through the introduction of methylated‐β‐cyclodextrin (Me‐β‐CD). The host‐guest interactions between Me‐β‐CD and photosensitive monomer (PM) were further investigated by 1HNMR and fluorescence spectroscopy, where the corresponding equilibrium constant was also calculated. Compared with pure PU, the tensile strength and thermal stability of UV‐curable PU films increased evidently. Furthermore, cotton fabrics treated by PU were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…From the 138 reviewed papers, twenty-seven (27) used polytetramethylene glycol (PTMG) as polyol [26,. Polypropylene glycol (PPG) was the second most chosen polyol, being part of twenty two studies [12,23,32,40,52,59,65,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82], followed by poly(ethylene glycol) (PEG) (sixteen studies) [7,21,73,[83][84][85][86][87][88][89][90][91][92][93][94][95][96], poly(ε-caprolactone) (PCL) (thirteen studies) [6,20,31,52,59,[97][98][99]...…”
Section: Literature Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…From the 138 reviewed papers, twenty-seven (27) used polytetramethylene glycol (PTMG) as polyol [26,. Polypropylene glycol (PPG) was the second most chosen polyol, being part of twenty two studies [12,23,32,40,52,59,65,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82], followed by poly(ethylene glycol) (PEG) (sixteen studies) [7,21,73,[83][84][85][86][87][88][89][90][91][92][93][94][95][96], poly(ε-caprolactone) (PCL) (thirteen studies) [6,20,31,52,59,[97][98][99]...…”
Section: Literature Analysismentioning
confidence: 99%
“…Simultaneously, high crosslinking density can prohibit the water molecular penetrating the inside of films and keep hydrophilic groups from moving towards the surface [141]. Reactive diluents as tripropyleneglycol diacrylate (TPGDA) [124,136], trimethylolpropane triacrylate (TMPTA) [83,96,106,109,137], pentaerythritol [50], pentaerythritol tetraacrylate (PETTA) [100], dipentaerythritol hexaacylate (DPHA) and dipropylene glycol diacrylate (DPGDA) [137,141], modified enzymes [134], trimethylolpropane tris(3-mercaptopropionate) (TMPMP) [149] among others can be added during UV-WPUs synthesis.…”
Section: Reactive Diluentsmentioning
confidence: 99%
“…With the help of principal component analysis, IR spectroscopic analysis indicated that the content of CO correlated with absorbance at 420 nm 25 . The increase in unsaturated bonds was beneficial to the fluorescence characteristics of black garlic MLDs 36 . However, the presence of unsaturated double‐carbon bonds weakened the water solubility of MLDs, and BG20 and BG40 showed stronger amplitudes.…”
Section: Resultsmentioning
confidence: 99%
“…25 The increase in unsaturated bonds was beneficial to the fluorescence characteristics of black garlic MLDs. 36 However, the presence of unsaturated doublecarbon bonds weakened the water solubility of MLDs, and BG20 and BG40 showed stronger amplitudes. The region around 1100 cm −1 was connected with C C, C O stretching and C H bending, which indicated the presence of glycosidic bonds in MLDs.…”
Section: Spectral Characteristics Of Black Garlic Mldsmentioning
confidence: 99%
“…Sagitha et al 16 investigated the changes in the physico‐chemical properties of β‐CD functionalized PU fiber membranes, it was found that all PU/CD membranes incorporating CD exhibited better hydrophilicity, thermal stability, higher vapor transfer rate, biocompatibility and PBS adsorption than the pristine PU membranes. Yao et al 17 prepared a different UV‐curable supramolecular WPUand investigated the effect of the amount of unsaturated bonds on hydrophilicity, thermal stability and mechanical properties, that the results showed that the polyurethane fabric based on the host‐guest interaction was more hydrophobic. Stefan et al 18 used a two‐step method to synthesize linear and crosslinking polyurethane materials containing β‐CD in their structure which was obtained with favorable mechanical properties for films with adsorption properties.…”
Section: Introductionmentioning
confidence: 99%